Henry Ettinghausen (2015): How the Press began. The Pre-periodical Printed News in Early Modern Europe - Díaz Noci, Javier (RIHC. Revista Internacional de Historia de la Comunicación, 2015)
How the Press began. The Pre-periodical Printed News in Early Modern Europe Henry Ettinghausen Janus,Anexo 3, 2015 303 pp.